Validation of Chinese medicine syndrome differentiation in early breast cancer: a multicenter prospective clinical study - Luo, Wei; Dai, Yan; Wu, Jiahua; Xue, Xiaohong; Liu, Lifang; Bian, Weihe; Xie, Xiaohong; Lyu, Gang; Hong, Ri; Qiu, Chang; Lin, Xiaojie; Xu, Rui; et al. (Frontiers in Oncology, 2026)
BackgroundBreast cancer is the most common cancer among women. Chinese herbal medicine, which is based on accurate Chinese medicine (CM) syndrome diagnosis, plays a vital role during cancer treatment. This study aimed to validate the established CM syndrome diagnostic criteria for early breast cancer, enhancing their application in clinical settings.MethodsA multicenter prospective clinical study was conducted to collect epidemiological data on CM syndromes. Two attending doctors from the CM breast department performed syndrome differentiation using established diagnostic criteria and compared it to two clinical experts with associate senior professional titles. Metrics such as sensitivity, specificity, and accuracy were utilized to assess the validity of the diagnostic test.ResultsA total of 641 eligible cases were enrolled from June 2022 to October 2023 from seven hospitals in China. The sensitivity rates for all syndromes ranged from 70.37% to 92.00%, with the highest rate for Spleen and Stomach disharmony in the postoperative stage. Specificity varied from 86.84% to 98.89%, with most criteria exceeding 90%. Overall accuracy of the diagnostic criteria was between 84.25% and 94.45%. Positive predictive values ranged from 72.22% to 98.21%, while negative predictive values spanned from 79.25% to 98.82%, with most syndromes above 80%. The concordance rate for diagnostic criteria ranged from 90.91% to 96.45%, with Kappa values between 0.747 and 0.926.ConclusionsThis study demonstrated that the diagnostic criteria exhibit high reliability, confirming the validity of CM syndrome diagnostic criteria among different treatment stages for early breast cancer and contributing to standardizing clinical practice.